Construction of a Super-Competent Bacillus subtilis 168 Using the PmtlA-comKS Inducible Cassette - Rahmer, Regine; Morabbi Heravi, Kambiz; Altenbuchner, Josef (Frontiers in Microbiology, 2015)
Competence is a physiological state that enables Bacillus subtilis 168 to take up and internalize extracellular DNA. In practice, only a small subpopulation of B. subtilis 168 cells becomes competent when they enter stationary phase. In this study, we developed a new transformation method to improve the transformation efficiency of B. subtilis 168, specially in rich media. At first, different competence genes, namely comK, comS and dprA, were alone or together integrated into the chromosome of B. subtilis 168 under control of mannitol-inducible PmtlA promoter. Overexpression of both comK and comS increased the transformation efficiency of B. subtilis REG19 with plasmid DNA by 6.7-fold compared to the wild type strain 168. This transformation efficiency reached its maximal level after 1.5 h of induction by mannitol. Besides, transformability of the REG19 cells was saturated in the presence of 100 ng dimeric plasmid or 3000 ng chromosomal DNA. Studying the influence of global regulators on the development of competence pointed out that important competence development factors, such as Spo0A, ComQXPA and DegU, could be removed in REG19. On the other hand, efficient REG19 transformation remained highly dependent on the original copies of comK and comS regardless of the presence of PmtlA-comKS. Finally, novel plasmid-free strategies were used for transformation of REG19 based on Gibson assembly.